Replication Data for: Adherence to preprints’ publication in Dentistry by Brazilian researchers - Cenci, Jaisson (2022)
The objective of this study was to evaluate the adherence to the preprint publication format by a sample of Brazilian researchers. The anonymized data set corresponds to the number of preprints published by all Brazilian researchers of graduate programs in dentistry (n=211) who were productivity fellows in 2021 (PQ) in three platforms: MedArxiv, OSF, and SciELO preprints.